Analysis of Medication Adherence Level and Influencing Factors in Hypertension Patients in Samarinda City - Sinta Ratna Dewi; Almahdy Almahdy; Hardisman Dasman; Syofyan Syofyan; Aldyba Syaqilla Hafifah (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Hypertension is a degenerative condition that significantly contributes to global morbidity and mortality, making medication adherence a critical factor in achieving long-term therapeutic success. This study investigates the relationship between patient-related factors and adherence to antihypertensive medication. A cross-sectional analytical survey was conducted among 195 hypertensive patients in Samarinda, East Kalimantan. Data were collected using a structured questionnaire incorporating the MMAS-8 scale, which categorizes adherence into high (score = 8), moderate (score = 6-7), and low (score < 6), alongside a validated instrument assessing sociodemographic, clinical, and behavioral determinants. Statistical analysis employed chi-square tests and odds ratios (OR) with 95% confidence intervals. The majority of patients demonstrated low adherence (65.6%), followed by moderate (28.7%) and high adherence (5.6%). Significant associations were found between adherence levels and gender (P = 0.033, OR = 0.513, 95% CI: 0.276-0.951), knowledge level (P = 0.013, OR = 2.190, 95% CI: 1.176-4.079), duration of hypertension (P = 0.017, OR = 0.483, 95% CI: 0.265-0.881), and insurance status (P = 0.004, OR = 0.080, 95% CI: 0.009-0.680). Knowledge level emerged as the most influential factor in promoting adherence. These findings highlight the importance of targeted educational interventions and sustained support for patients at risk of poor adherence, aiming to optimize antihypertensive therapy and prevent long-term complications. The study advocates for strengthened evidence-based clinical practices and underscores the need for health policy reforms particularly in patient education and insurance accessibility to improve hypertension management in primary care settings. Keyword: Adherence, Hypertension, Gender, Knowledge